Opinion Polls and The Measurement of Public Opinion Petween Pheoretical Principles and Practical Problems- Reading in The Results of The Survey To Promote English in The University and Research community in Algeria - gherabi , abdesselem; berardi, naima (Journal of Social Sciences and Humanities, 2022)
This inductive descriptive Study identified an important media/political issue, linked to the measurement of opinion polls and their mechanisms of action, as as part of the accelerated processes of transition to the information society and the knowledge industry began to show new practices to measure public opinion over the Internet, and despite its positives, it affected the ethics of scientific research and met scientific and professional standards. Although the results of the survey promoting English in the university and research community in Algeria are effective, they have been linked to several problems: methodology, cultural, artistic, objective, and political. They can be overridden to make public opinion surveys achieve their goals of democratic reform at various levels.